Folic Acid: Sources, Chemistry, Absorption, Metabolism, Beneficial Effects on Poultry Performance and Health - Herinda Pertiwi; Mohamad Yusril Nur Mahendra; Juriah Kamaludeen (Veterinary Medicine International)
Recently, there has been an increasing interest in the study of the effects of folic acid (FA) on poultry because it was observed that FA could overcome problems in poultry health while improving its performance. FA, or folate, is a water-soluble B vitamin essential in poultry, so FA intake must be available in the feed. Sources of FA in feed come from plants or animals, and animal sources have relatively more stable FA. The ingested FA will be absorbed in the intestinal lumen and transported into the liver through the blood vessels. Therefore, FA has a positive effect on the performance and health status of poultry. The effect of FA on poultry performance is to increase reproductive tract development, FA content in eggs, hatchability, weight gain, average initial body weight, feed intake, relative growth rate, chick body weight, breast fillet percentage, and reduce FCR and white striping score. At the same time, the effect on poultry health influences antioxidant activities, thyroid hormones, blood biochemicals, anti-inflammatory gene expressions, and immune responses. The present review deals with FA sources, chemistry, absorption, metabolism, effects on performance, and poultry health, which are based on valid basic information.